Excavations and Foundations in Soft Soils - Kempfert, Hans-Georg; Gebreselassie, Berhane (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The book is about soft soil engineering and is intended to serve the practicing as well as the research engineers. The planning, design and construction of exca- tions and foundations in soft to very soft soils is always a difficult and challanging assignment to engineers. The authors have tried to address some of these problems and challenges in this book. Beside the state of the art of soft soils, authors own research results and expe- ences from practical projects are presented in the book. Special emphasis is also given among others on the presentation of several case studies coresponding to each topic treated in the book as well as a summary of the experiences in the - termination of soil parameters for finite element analysis of geotechnical pr- lems. The book is illustrated by a wealth of photographs and diagrams. The reader is refered to chapter 1 for a general introduction to the content of the book, the motives and backgrounds of the book. The aim of the authors is to give the readers an overview of the state of the art of material properties of soft soils and their application in excavations, different types of foundations and stabilization methods. The authors emphasis, however, that the presence of soft soil in connection with construction measure should not a priori be classified as extremely difficult and strong cost intensive for the project.